Visuality and Materiality: The Problem of Image and (Con)Text - Martínez Luna, Sergio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2014)
The article seeks to study the relationship between visuality and materiality. Visual Studies show an increasing interest in understanding the material dimension of images. The article stresses the need to understand the concepts of text and context as negative and problematic. A simple shift from text to context is insufficient for Visual Studies, which consider visuality as a no-self-evident concept. For this reason the validity of the concept is reviewed in order to maintain its critical force. Likewise it is recalled that the concept of text, far from being a tool for epistemological clarification, may end up adding new layers of complexity to research. The paper invites to understand social and narrative practices as articulated with a multitude of domains, realities, and material and social worlds. Accordingly it is argued that the study of the intersections between the material and the visual should abandon any dualistic logic in order ...